Patient preferences for healthcare delivery through community pharmacy settings in the USA: A discrete choice study. - Feehan, M.; Walsh, M.; Godin, J.; Sundwall, D.; Munger, M. A. (Journal of Clinical Pharmacy & Therapeutics, 2017)
What is known and objective In order to improve public health, it is necessary to facilitate patients' easy access to affordable high-quality primary health care, and one enhanced approach to do so may be to provide primary healthcare services in the community pharmacy setting. Discrete choice experiments to evaluate patient demand for services in pharmacy are relatively limited and have been hampered by a focus on only a few service alternatives, most focusing on changes in more traditional pharmacy services. The study aim was to gauge patient preferences explicitly for primary healthcare services that could be delivered through community pharmacy settings in the USA, using a very large sample to accommodate multiple service delivery options. Methods An online survey was administered to a total of 9202 adult patients from the general population. A subsequent online survey was administered to 50 payer reimbursement decision-makers. The patient survey included a discrete choice experiment ( DCE) which showed competing scenarios describing primary care service offerings. The respondents chose which scenario would be most likely to induce them to switch from their current pharmacy, and an optimal patient primary care service model was derived. The likelihood this model would be reimbursed was then determined in the payer survey. Results and discussion The final optimal service configuration that would maximize patient preference included the pharmacy: offering appointments to see a healthcare provider in the pharmacy, having access to their full medical record, provide point-of-care diagnostic testing, offer health preventive screening, provide limited physical examinations such as measuring vital signs, and drug prescribing in the pharmacy. The optimal model had the pharmacist as the provider; however, little change in demand was evident if the provider was a nurse-practitioner or physician's assistant. The demand for this optimal model was 2-fold higher (25.5%; 95% Bayesian precision interval ( BPI) 23.5%-27.0%) than for a base pharmacy offering minimal primary care services (12.6%; 95% BPI 12.2%-13.2%), and was highest among Hispanic (30.6%; 95% BPI: 25.7%-34.3%) and African American patients (30.7%; 95% BPI: 27.1%-35.2%). In the second reimbursement decision-maker survey, the majority (66%) indicated their organization would be likely to reimburse the services described in the optimal patient model if provided in the pharmacy setting. What is new and conclusion This United States national study provides empirical support for a model of providing primary care services through community pharmacy settings that would increase access, with the potential to improve the public health.